Green initiatives and its reflection on green human resource management in IT companies - V.J., DR. MAHESH; T, MR. GAUTHAM. (The journal of contemporary issues in business and government, 2020)
The research paper titled a Study on green initiatives and its reflection on green human resource management in IT Company. Descriptive research is applied using a simple random method of sampling with 74 respondents. The main aim of this paper is to show the impact of green human resource and its practices in the IT industry. Green Human Resource Management (GHRM) is a set of practices used by a company to reduce its carbon footprint. It has been observed that there is an increased awareness within the business environment on the motivation on going green and adopting various techniques to manage the environment. GHRM is a budding concept which is ready to explore green economic sides of business as the business world is going global. It is important for the company to follow GHRM to maintain its image by being an eco -friendly company which results in greater efficiency, low costs and better employee engagement and retention. It is found that practicing GHRM is influenced by factors like Green focus on CSR, Green Recruitment and Selection, Green Training and Development, Green Transportation, Green Printing, E-filing and Energy savings.